The Impact of Banks’ Reserves on their Financial Performance Comparative Study between Islamic and Conventional banks in Jordan - Milhem, Maysa’a; Abu Mousa, Rasmiah (Jordan Journal of Economic Sciences, 2020)
This study aimed to test the effect of reserves in Islamic and Conventional banks on financial performance measured by profitability, liquidity and risk. The sample included thirteen conventional banks and two Islamic banks. The study concluded that there is a statistically significant impact of reserves on the financial performance of Islamic and conventional banks, while there is no statistically significant difference between the profitability of conventional banks and Islamic banks. It also presented evidence confirming the significant difference between the liquidity of conventional banks and Islamic banks, and the risks of conventional banks are higher than those of Islamic banks.